Prevalance of HIV in Children with Severe Acute Malnutrition Admitted in Children Hospital PIMS (Indus Journal of Bioscience Research, 2025)
Background: Malnutrition contributes to about half of the mortality in children. HIV infection in children suffering from severe acute malnutrition (SAM) is a major health concern, especially in areas where both illnesses are prevalent. HIV and malnutrition have a synergistic effect on the immune system and general health, increasing risk of death and major complications. Our study focuses on finding prevalence of HIV infection in children admitted with severe acute malnutrition in a tertiary care hospital in Pakistan. Methodology: After taking informed consent from parents/guardians 140 children aged 6month to 5 years admitted with SAM were enrolled. After counselling of parents regarding HIV testing and written consent patients were tested for HIV via rapid HIV antibody test. If a child was found to be positive for HIV their parents were tested for HIV and the child registered in HIV center for management. The demographic data, HIV test results and anthropometric measurements of patients were entered in a preformed performa and data analyzed using SPSS 27. Results: In our study, 6 patients (4.3%) out of the 140 children admitted with severe acute malnutrition, had HIV. All SAM patients with HIV had a vertical HIV transmission pathway. Compared to the overall HIV incidence in Pakistan, the prevalence of HIV among children with SAM is significantly higher. Conclusion: Children who suffer from severe acute malnutrition are far more likely to be HIV-positive, this necessitates routine HIV screening.